KLASIFIKASI DAN IDENTIFIKASI PLAT NOMOR GANJIL-GENAP DENGAN MENGGUNAKAN METODE JARINGAN SYARAF TIRUAN - BIMO PRASETYO (2020)
With the large number of vehicles in Indonesia, especially in big cities, the government restricts vehicles to even odd-numbered license plates, so a special camera is needed to detect license plates, based on the purpose of this study in order to find out how the system works. By using several processes viz, the process of cropping, resizing, greyscale, noise removal and binarization after the data is processed or the data collected has been carried out at a later stage. By using Artificial Neural Networks to train and recognize the characters in the OCR Trainer programmed using matlab so that the accuracy of character recognition is up to 96.875%.